(untitled) (Bangladesh Critical Care Journal, 2021)
Pancytopenia is a condition where all three types of blood cell counts simultaneously become low. There are multiple factors for which pancytopenia might occur, however pancytopenia because of Covid-19 have been reported rarely. Here, we discussed a case of pancytopenia, which presented to us as a consequence of Covid-19 infection. Bangladesh Crit Care J September 2021; 9 (2): 118-120